2014
DOI: 10.1093/jrr/rru087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and the window of radioprotection for adrenergic and serotoninergic agents and aminothiols in experiments with small and large animals

Abstract: This review gives a comparative evaluation of the radioprotective properties and the therapeutic index (TI) of radioprotectors from various pharmacological group in experiments on both small and large animals. It presents a hypothesis explaining the decrease in the TI of cystamine and 5-methoxytryptamine (mexamine), and the retention of that of α1-adrenomimetic indralin, and also compares the effects on large and small animals. The considerable differences in the therapeutic indices of catecholamines, serotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
2
5
0
1
Order By: Relevance
“…2). This is consistent with published reports indicating that Am and WR can effectively reduce but not block an absorbed radiation dose (Junn et al 2012; Vasin and Ushakov 2015).…”
Section: Discussionsupporting
confidence: 93%
“…2). This is consistent with published reports indicating that Am and WR can effectively reduce but not block an absorbed radiation dose (Junn et al 2012; Vasin and Ushakov 2015).…”
Section: Discussionsupporting
confidence: 93%
“…For example, a decrease in the tryptophan and histidine metabolism, including tryptophan, serotonin, and histamine values, was reported in studies using mouse serum, mouse intestine, and rat urine [25][26][27][28][29]. These metabolites were reported to function as radioprotectors [30][31][32], and we observed that a decrease in these radioprotective metabolites helped explain the radiation-induced damage. We also observed a decrease in the components of the pyrimidine metabolism pathway, such as thymidine, in TBI mice, although several previous studies using mouse serum and urine showed that TBI upregulated the levels of thymidine, reflecting DNA or RNA damage [26,33].…”
Section: Discussionsupporting
confidence: 65%
“…administration—1/16–1/10 LD 10 ( Table 2 ). Such pharmacological ratios show the advantage of T1082 in comparison with many known radioprotective agents [ 25 ]. This allows for its classification as one of the safest radioprotectors with an emergency, preventive effect.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the T1082 therapeutic index (LD 50 /ED 50 ) reaches 30, and its optimal radioprotective doses (ED 84-98 —141–224 mg/kg) are an order of magnitude lower than the maximum tolerated doses—1/16–1/10 LD 10 . These data allow for the classification of T1082 as one of the safest radioprotectors with emergency, preventive action [ 25 ].…”
Section: Discussionmentioning
confidence: 99%